Translation and silencing in RNA granules: a tale of sand grains - Pimentel, Jerónimo; Boccaccio, Graciela L. (Frontiers in Molecular Neuroscience, 2014)
The transcriptome at the synapse consists of thousands of messengers encoding several cellular functions, including a significant number of receptors and ion channels and associated proteins. The concerted translational regulation of all these molecules contributes to the dynamic control of synaptic strength. Cumulative evidence supports that dendritic RNA granules and mRNA-silencing foci play an important role in translational regulation. Several relevant RBPs – FMRP; FUS/TLS; TDP-43; Staufen; Smaug; Pumilio; CPEB; HuD; ZBP1; and DDX6 among others – form granules that contain dormant mRNAs repressed by multiple pathways. Recent reports indicate that dendritic granules may contain stalled polysomes, and furthermore, active translation may occur in association with RNA granules. Here, we discuss the molecules and pathways involved in this continuum of RNA granules that contain masked mRNAs, mRNAs trapped in inactive polysomes or mRNAs engaged in translation.